Robert Morton interviewed by Rob Willis in the Rob and Olya Willis folklore collection - Morton, Robert, 1941-; Morton, Lynn.; Willis, Rob, 1944- (2008)
Folkloric recording. Bob Morton talks about his early childhood memories of his father, Tex Morton; the separation of his parents; growing up in Bondi; school days; surf culture of the area and that era; his work history; his musical interests and direction; his relationship with his father up until his death in 1983; learning the harmonica; playing in a Blues band. He finishes off the interview with some tunes on the blues harp.
Plays: Mangrove mountain riff -- several unidentified riffs on the harmonica.
Recorded by John Harpley.
Lynn Morton also present during interview.
Recorded on December 4, 2008 at Wyong, N.S.W.
Digital master available
Bob Morton, is the son of the late country music performer, Tex Morton.
Timed summary available.
Keywords: Morton, Robert, -- 1941- -- Interviews; Morton, Tex, -- 1916-1983 -- Anecdotes; Musicians -- New South Wales -- Interviews; Surfing -- New South Wales -- Bondi; Surfing -- Social aspects -- New South Wales -- Bondi; Musicians